Association of Cerebrospinal Fluid Parameters and Neurofilament Light Chain With Retinal Nerve Fiber Layer Thickness in Multiple Sclerosis - Krajnc, Nik; Altmann, Patrick; Riedl, Katharina; Mitsch, Christoph; Berger, Thomas; Leutmezer, Fritz; Rommer, Paulus; Pemp, Berthold; Bsteh, Gabriel (Frontiers in Neurology, 2022)
Introduction. Multiple sclerosis (MS) pathophysiology comprises both inflammatory and neurodegenerative characteristics. Cerebrospinal fluid (CSF) analysis allows for assessment of inflammation while neurofilament light chain can indicate neuroaxonal damage. Retinal thinning is a robust prognostic biomarker for neurodegeneration in MS. To date, an association between CSF parameters upon MS diagnosis and retinal thinning has not been investigated. Aims and objectives. We aimed to determine whether CSF parameters are associated with the evolution of retinal layer thinning in people with MS (pwMS). Methods. For this longitudinal observational study, we investigated pwMS from the Vienna MS database (VMSD), who had undergone 1) a diagnostic lumbar puncture (LP) between 2015-2020, and 2) simultaneous optical coherence tomography (OCT) and/or 3) a follow-up OCT scan. Linear stepwise regression models were calculated with OCT parameters (peripapillary retinal nerve fiber layer [pRNFL] thickness at LP and at follow-up, annualized loss of pRNFL thickness [aLpRNFL]) as a dependent variable, and CSF parameters (white blood cell [WBC] count, total protein [CSFTP], CSF/serum albumin ratio [Qalb], intrathecal synthesis of immunoglobulins, neurofilament light chain [NfL] in both CSF and serum [CSFNfL/sNfL]) as independent variables adjusted for age, sex and disease duration. Results. We analyzed 61 pwMS (median age 30.0 years [interquartile range 25.5–35.0], 57.4% female, median disease duration 1.0 month [IQR 0–2.0] before LP, median follow-up 1.9 years [IQR 1.1–3.5]). CSFNfL and sNfL measurements were available in 26 and 31 pwMS, respectively. pRNFL thickness at LP was inversely associated with the CSF WBC count (β= –0.36; 95% CI –0.51, –0.08; p=0.008). We did not find any association between other CSF parameters, including CSFNfL, sNfL and aLpRNFL. Conclusions. Increased WBC count as an indicator of acute inflammation and blood-brain-barrier breakdown seems to be associated with the amount of retinal thickness already lost at the time of LP. However, neither routine CSF parameters nor a singular NfL measurement allow prediction of future retinal thinning.